1992
DOI: 10.1073/pnas.89.8.3389
|View full text |Cite
|
Sign up to set email alerts
|

The threshold induction temperature of the 90-kDa heat shock protein is subject to acclimatization in eurythermal goby fishes (genus Gillichthys).

Abstract: Two extremely eurythermal goby fishes, Gillichthys mirabilis and Giffichthys seta, which encounter habitat temperature variations of "30"C, showed seasonal matization of endogenous levels and of onset temperatures for enhanced synthesis of a 90-kDa-class heat shock protein (HSP90). Summer-acclimatized fishes had higher levels of HSP90 in brain tissue than winter-acclimatized specimens, as shown by Western blot analysis. For winter-acclimatized fishes, increased synthesis of HSP90 was observed when the temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
103
1
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(116 citation statements)
references
References 9 publications
10
103
1
2
Order By: Relevance
“…Hofmann and Somero (1995) showed seasonal patterns of HSP70 and ubiquitin expression for acclimatization in the mussel Mytilus edulis. Additional examples of seasonal expression of HSPs are known from other organisms (Dietz and Somero, 1992). However, to the best of our knowledge, this is the first report of seasonal expression of HSPs in benthic marine Anthozoans.…”
Section: Discussionmentioning
confidence: 63%
“…Hofmann and Somero (1995) showed seasonal patterns of HSP70 and ubiquitin expression for acclimatization in the mussel Mytilus edulis. Additional examples of seasonal expression of HSPs are known from other organisms (Dietz and Somero, 1992). However, to the best of our knowledge, this is the first report of seasonal expression of HSPs in benthic marine Anthozoans.…”
Section: Discussionmentioning
confidence: 63%
“…This is of particular interest in dermatology where the inducer could be used topically and should not lose its effect upon repeated application. Adaptation to the set point of the heat shock response has been described in yeast and fish, and in a Drosophila model the expression of a transgene under control of the hsp70 promoter is reduced after repeated heat shocks (Dietz and Somero 1992;Hunt et al 1992;Carratu et al 1996). Very little information is available about the consequences of repeated stress exposure in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in several populations and species have shown that there is a great variation in HSP expression patterns, mainly in three types of categories: as a function of thermal history, correlating to microhabitat, and between species . These types of studies have been performed in several marine organisms such as fish (e.g., Dietz and Somero 1992;Norris and Hightower 2002;Buckley and Hofmann 2002;Fangue et al 2006), bivalves (e.g., Chapple et al 1998;Buckley et al 2001;Helmuth and Hofmann 2001;Encomio and Chu 2005), snails (e.g., Somero 1999, 2002;Tomanek and Sanford 2003;Clark and Peck 2009), and crustaceans (e.g., Botton et al 2006;Kelley et al 2011). Since most of the studies on intraspecific differences in thermal tolerance focus on latitudinal, intertidal distribution, and seasonal comparisons (see Hofmann 1999), it is important to approach intraspecific differences that have been less explored in marine organisms, especially sex and size differences.…”
Section: Introductionmentioning
confidence: 99%